Implementation of NAMS Cycle Model– a continuous Improvement model from Islamic perspective - Afrin, Afroza Bulbul; Islam, Rafikul; Ali, Md. Yousuf (Universiti Putra Malaysia Press, 2020)
The main objective of this research is to develop an implementation process of the newly developed continuous improvement (CI) model – NAMS Cycle. Erecting on the affirmative postmodernism philosophy, fundamental epistemological foundations of this research are the Qur’ān and the Sunnah of the Prophet (peace be upon him) and the contributions of scholars in Islam. A qualitative methodology is adopted to conduct this research. Data were collected through focus group discussions (FGD) and semi-structured in-depth interviews and were analysed manually. Based upon the data, the researchers have finalised a five-step implementation process of the NAMS cycle started with decision making and followed by education and training, implementation, evaluation, and corrective measures. Departmental Heads and all the employees will be involved to implement the model successfully.